Spike-Timing-Dependent Plasticity Mediated by Dopamine and its Role in Parkinson’s Disease Pathophysiology - Madadi Asl, Mojtaba; Vahabie, Abdol-Hossein; Valizadeh, Alireza; Tass, Peter A. (Frontiers in Network Physiology, 2022)
‎Parkinson's disease (PD) is a multi-systemic neurodegenerative brain disorder‎. ‎Motor symptoms of PD are linked to the significant dopamine (DA) loss in substantia nigra pars compacta (SNc) followed by basal ganglia (BG) circuit dysfunction‎. ‎Increasing experimental and computational evidence indicates that (synaptic) plasticity plays a key role in the emergence of PD-related pathological changes following DA loss‎. ‎Spike-timing-dependent plasticity (STDP) mediated by DA provides a mechanistic model for synaptic plasticity to modify synaptic connections within the BG according to the neuronal activity‎. ‎To shed light on how DA-mediated STDP can shape neuronal activity and synaptic connectivity in the PD condition‎, ‎we reviewed experimental and computational findings addressing the modulatory effect of DA on STDP as well as other plasticity mechanisms and discussed their potential role in PD pathophysiology and related network dynamics and connectivity‎. ‎In particular‎, ‎reshaping of STDP profiles together with other plasticity-mediated processes following DA loss may abnormally modify synaptic connections in competing pathways of the BG‎. ‎The cascade of plasticity-induced maladaptive or compensatory changes can impair the excitation-inhibition balance towards the BG output nuclei‎, ‎leading to the emergence of pathological activity-connectivity patterns in PD‎. ‎Pre-clinical‎, ‎clinical as well as computational studies reviewed here provide an understanding of the impact of synaptic plasticity and other plasticity mechanisms on PD pathophysiology‎, ‎especially PD-related network activity and connectivity‎, ‎after DA loss‎. ‎This review may provide further insights into the abnormal structure-function relationship within the BG contributing to the emergence of pathological states in PD‎. ‎Specifically‎, ‎this review is intended to provide detailed information for the development of computational network models for PD‎, ‎serving as testbeds for the development and optimization of invasive and non-invasive brain stimulation techniques‎. Computationally derived hypotheses may accelerate the development of therapeutic stimulation techniques and potentially reduce the number of related animal experiments.